(untitled) (Research, Society and Development, 2020)
The school is an ideal space to implement and strengthen preventive attitudes in cases of accidents involving toxic plants with children. However, that same space has offered different types of risks. With this, we seek to analyze the conceptions of teachers of early childhood education about toxic plants present in the school environment. To this end, an exploratory and descriptive research, with a qualitative approach, was carried out with twenty teachers of early childhood education in the municipality of Aldeias Altas, located in the eastern region of the state of Maranhão, Brazil. The analysis took place from two categories. The first “Recognizing a toxic plant”, describes how the participants perceive toxic plants in the school environment, and the second, “Strategies and care in accidents with toxic plants”, outlines which elements are triggered (or not), in cases of accidents with children. Finally, the teachers recognized some gaps in this process, mainly in training, but it is worth noting that the education system involves structural, cultural, social and economic issues that are directly related to the ethos of teaching work.